Estudo do hidróxido de cálcio associado ou não à clorexidina como medicação intracanal de dentes permanentes necrosados - Dias, Françoise Parahyba (2010)
Aware that the main objective of endodontic treatment is the removal of microorganisms and the prevention of re-infection inside the root canal, and that the infections are polymicrobial and difficult to eliminate, the biomechanical preparation is essential for disinfection, though it is unable to eradicate all microorganisms. The intracanal medication is used as an adjunct to treatment, reducing the endodontic microbiota, and favoring the repair of periapical lesions. However, this dissertation consists of two papers and it is proposed, through a written review, to examine and discuss the intracanal medications most frequently used at present in endodontics - calcium hydroxide and chlorhexidine. Further, through research, to evaluate the antibacterial effect of biomechanical preparation and a calcium hydroxide based paste containing or not 2% chlorhexidine, as intracanal medication in the treatment of necrotic teeth after trauma, as well as to verify the presence of the microorganisms Fusobacterium nucleatum and black-pigmented bacilli inside the root canal of teeth. According to the inclusion criteria, the sample consisted of 14 incisors necrotic after trauma. The microbiological samples were acquired before (S1) and after biomechanical preparation (S2), after intracanal medication (S3) and 72 hours after removal of medication (S4). Selected at random, eight patients used calcium hydroxide as intracanal medication and six patients the calcium hydroxide based paste containing 2% chlorhexidine. The samples were collected sequentially, inserting three sterile absorbent paper cones with a diameter compatible with the root canal, and after a minute the paper points were removed and placed in a tube containing a reduced transport fluid, and sent to the laboratory for microbiological evaluation. The results were analyzed by the Friedman, Conover-Inman and Kruskal-Wallis tests (p <0.05). Microorganisms were found in 100 % of root canals in the initial samples (S1), while in S2 were detected in only 3 out of the 14 samples (21.4 %), resulting in a reduction in the number of colony forming units, a statistically significant result (p <0.001) between S1 and S2. No statistically significant reduction was observed when comparing S2 with S3, S2 with S4, and S3 with S4, regardless of the medication used. It was found that in S1, there was a predominance of Gram-positive cocci - 8 out of 14 (57.1 %) and Gram-negative cocci - 9 out of 14 (64.3 %). In S2 only Gram-positive bacterial morphotypes were detected, in 3 out of 14 samples (21.4 %) of Gram-positive cocci and 2 out of 14 (14.3%) of Gram-positive bacilli. The microorganisms Fusobacterium nucleatum found in 8 of the 14 samples (57.1%) and the black-pigmented bacilli found in 3 of the 14 (21.4%) of the initial samples, and were found in only one out of 6 (16.1%) samples taken after the use of calcium hydroxide. It was concluded that mechanical preparation of necrotic teeth after trauma, using 2.5% NaOCl, plays its role in significantly reducing the microbiota of root canals, but the calcium hydroxide, or the calcium hydroxide based paste containing 2% chlorhexidine, have a limited antibacterial effect, not being able to prevent the re-growth of bacteria after its use as an intracanal medication.